Does a comprehensive service user-led education programme effect more positive attitudes towards recovery and less stigmatising attitudes towards people with lived experience of mental distress in medical students? A comparative cohort study. (September 2021) - Newton-Howes, Giles; Senior, Jessica; Beaglehole, Ben; Purdie, Gordon L; Gordon, Sarah E
Objective: This study sought to investigate the impact of a service user-led anti-stigma and discrimination education programme, encompassing numerous interventions focused on facilitating multiple forms of social contact, the promotion of recovery, and respect for human rights, on medical student attitudes. Method: A comparison cohort study was used to compare the attitudes of two cohorts of medical students who received this programme as part of their fifth (the fifth-year cohort) or sixth (the sixth-year cohort) year psychological medical education attachment (programme cohorts) with two cohorts of equivalent students who received a standard psychological medical attachment (control cohorts). Attitudes to recovery (using the Recovery Attitudes Questionnaire) and stigma (using the Opening Minds Scale for Healthcare Providers) were measured at the beginning and end of the attachments for each year and compared both within and between the cohorts using Wilcoxon signed-rank or Wilcoxon rank-sum tests. Results: With sample sizes ranging from 46 to 70 across all cohorts, after their psychological medicine attachment both the programme and control cohorts showed more positive attitudes towards recovery and less stigmatising attitudes towards people with lived experience of mental distress. Significant differences between the programme cohorts and the control cohorts were found for recovery attitudes (median difference of 2, p  < 0.05 in both fifth and sixth year), with particularly large differences being found for the 'recovery is possible and needs faith' subdomain of the Recovery Attitudes Questionnaire. There were no significant between cohort differences in terms of stigmatising attitudes as measured by the Opening Minds Scale for Healthcare Providers. Conclusion: The introduction of a comprehensive service user-led anti-stigma and education programme resulted in significant improvements in recovery attitudes compared to a control cohort. However, it was not found to be similarly superior in facilitating less stigmatising attitudes. Various possible reasons for this are discussed.